SEARCHING FOR INDICATORS OF THE EXISTENCE OF SUPERMASSIVE BINARY BLACK HOLES IN X-RAY RANGE USING NUSTAR MISSION DATA AT BLAZAR MKN 501 AND 3C 279 - Nurlita Agustin, Vinsi
Active Galactic Nuclei (AGNs) are nucleus of galaxy that are very active in producing enormous energy. AGN can have jets and are commonly known as jetted-AGNs, one of which is a blazar. There are a number of blazars that are suspected of having double supermassive black hole at the center or a supermassive binary black hole (SBBH). This multiplicity is indicated by the periodicity of the light curve, variations in optical polarization, or spectral variability. In the X-ray range, the blazar spectrum is generally dominated by radiation from jets. However, if the blazar is SBBH, then the interaction effect of the two supermassive black holes is expected to be observed, at least in one of the spectral ranges. The objectives of this Final Project are: 1) To study the observational characteristics of blazar supermassive binary black hole candidates, especially blazars MKN 501 and 3C 279; 2) To study the variability of the X-ray spectrum for MKN 501 and 3C 279 using NuSTAR mission data; 3) To study the indications of the existence of supermassive binary black holes based on spectrum analysis of the NuSTAR X-ray mission data for MKN 501 and 3C 279. To achieve these three objectives, NuSTAR mission observation data were processed on all observations that could be processed. The observed data were then analyzed based on the features on the light curve, hardness intensity diagram, and the X-ray spectrum. The spectrum model used in this Final Project is the powerlaw and log parabola which is a simple model commonly used to model non-termal radiation in X-ray. The model used is statistically suitable. With the NuSTAR X-ray spectrum and no additional components are found separately from the main radiation components of the blazar in general. These results indicate that there is no indication of the interaction between the supermassive black hole in the two objects of this Final Project study. However, further studies need to be done considering the limited X-ray data available at this moment.